The role of spiritual leadership in reducing organizational silence: An analytical study of the views of academic leaders in the colleges of the Salahaddin University– Erbil - Nehayat saady rahman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The research seeks to identify the spiritual leadership and its dimensions of (Vision, altruism and organizational commitment) Plus their roles in reducing organizational silence. The research was conducted among the academic leaders working in the colleges of the Salahaddin University in the city of Erbil. The research problem was identified by asking questions centered on the nature of the relationship and the effects between the variables. A hypothetical diagram was designed that shows the main hypotheses of the research. In the meantime, a questionnaire was used as a means to obtain the data that was distributed to the academic leaders in colleges, consisting of (100) leaders, were at the end (92) complete questionnaires were retrieved valid for analysis. In order to validate the hypotheses, the research has undergone multiple tests using the SPSS-V.22 a statistical program. The research adopted the descriptive method for the analysis of the results. Finally, the research reached several conclusions, the most important of which is the existence of a positive relationship and moral effect between the two research variables. The research came out with the necessity of enhancing the concept and uses of spiritual leadership and its modern methods also the necessity of educating the members of the organization on the importance of practicing the voice in expressing opinions and ideas related to the problems and difficulties of work they face by activating communication channels between the heads and supervisors of the departments and the other employees, thus giving the members of the organization a higher ceiling of freedom to express their opinions and ideas related to their work problems.